DYNAMIC CAPABILITIES:Agility and Competitive Approach in a Dynamic Environment: - Sebuwufu , Joseph Awali (My University, 2012)
In this decade, many firms especially Small and Medium Enterprises (SMEs) face challenges of turbulent environments. The main characteristic of such environment challenging SMEs is stiff competition from other companies. Many Small and Medium Enterprises, due to their uniqueness, end up getting bankrupt when faced with the challenges of the turbulent environment. There is a need to contribute to the development of strategies that supports SMEs. This study uses the sense-and-respond in the Balanced Critical Factor Index (BCFI) method to analyse and normalise the critical attributes (key performance indicators) responsible for performance in SMEs. The ideology of this method and study extends on the dynamic agile innovation in dynamic capabilities sustainability strategies that SMEs use in generating, reconfiguring, managing, integrating and re-allocating resources appropriately to stay afloat. In the literature, there are suggestions for SMEs that they can adapt when faced with challenges associated with turbulent environment. Although sometimes SMEs may be working for larger companies, their challenges will still be in their supply chain, or the free market-entry. However, the literature suggests strategies that SMEs can adapt to stay afloat. In addition, the BCFI method used in the study is proved worthy on two different case studies, from different business sector. Both case results showed positive results and those from the first case study, have been implemented in the housing sector. This implies that, although many of these dynamic capabilities favour large firms, they can be adapted and applied to SMEs for similar purposes with positive results.
Keywords: Dynamic capability; SMEs; Sense-and Respond; Technology; Management; Performance.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|